Primary care management of hidradenitis suppurativa: a cross- sectional survey of UK GPs. Issue 5 (2021) - Collier, Fiona; Howes, Rachel; Rodrigues, Jeremy; Thomas, Kim S; Leighton, Paul; Ingram, John R
No abstract available